A Holistic Evaluation of Qualitative Research Course by Graduate Students and Academic Staff - Yağmur Şahin; Selami Uysal; Lütfi Saraç; Kerim Gündoğdu (Anı Publishing, 2019)
In this study, it is aimed to have those graduate students who are taking the qualitativeresearch and those professors who are giving the course at the department of Educational Sciences, in the faculty of Education of a public university evaluate the course and previous courses in depth, depending on different variables. 18 postgraduate students and 3 professors participated in the study on a voluntary basis in the Department of Educational Sciences of the related university. Data were obtained through interviews, observations and documents in order to provide data triangulation, and content analysis was used in the analysis of the data. As a result of the research, it was seen that graduate students consider qualitative research methods important within the field of educational sciences; negative opinions about the physical environment in which the course is taught; computer, projection, thesis, articles and books are mostly used as tools and materials in the course; the presence of a course outline is found to be positive. It was also concluded that student presentations, product based studies, assignments and exams were generally included in the evaluation of the students'success.